2020
DOI: 10.3389/fchem.2020.00778
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Fabrication of Zinc Oxide Nanoparticles and Evaluation of Their Antimicrobial and Photocatalytic Properties

Abstract: Zinc oxide (ZnO) nanoparticles have attracted significant interest in a number of applications ranging from electronics to biomedical sciences due to their large exaction binding energy (60 meV) and wide bandgap of 3.37 eV. In the present study, we report the low-cost bacterium based "eco-friendly" efficient synthesis of ZnO nanoparticles by using the zinc-tolerant bacteria Serratia nematodiphila. The physicochemical characterization of ZnO nanoparticles was performed by employing UV-vis spectroscopy, XRD, TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…13,14 Previous studies have reported that RGO has antimicrobial activity, [15][16][17] and GO when conjugated with active ingredients exhibits antimicrobial and antinematodal activities. 18,19 Furthermore, metal and metal oxide nanoparticles, such as silver, [20][21][22] zinc oxide, [23][24][25] and nickel oxide, 26,27 are widely used as antimicrobials, and a silver boron nano-formulation is a potential nematicide. 28 Furthermore, RGO-based metal oxide nanocomposites have garnered much attention as antimicrobials in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Previous studies have reported that RGO has antimicrobial activity, [15][16][17] and GO when conjugated with active ingredients exhibits antimicrobial and antinematodal activities. 18,19 Furthermore, metal and metal oxide nanoparticles, such as silver, [20][21][22] zinc oxide, [23][24][25] and nickel oxide, 26,27 are widely used as antimicrobials, and a silver boron nano-formulation is a potential nematicide. 28 Furthermore, RGO-based metal oxide nanocomposites have garnered much attention as antimicrobials in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans biofilm formation was also inhibited by the CS/Ag/ZnO nanocomposite at 50 ÎŒg mL –1 (92%) ( Thaya et al, 2016 ; Vijayakumar et al, 2019 ). Jain et al (2020) successfully synthesized ZnO nanoparticles that had excellent antimicrobial activity and applicability against Xanthomonas oryzae pv. oryzae and Alternaria sp.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Jain et al, 2020 biosynthesized ZnONPs using the zinc-resistant bacterium Serratia nematodiphila and, in vitro, tested the antimicrobial activity of ZnONPs against Xanthomonas oryzaepv. oryzae [ 224 ]. Xanthomonas oryzaepv.…”
Section: Applications Of Nanoparticlesmentioning
confidence: 99%